Pengaruh Kualitas Produk Dan Saluran Distribusi Terhadap Volume Penjualan Pada CV. Citra Abadi (CA) Bandar Lampung - Wahyudi, Asep Nur; Isabella, Astrid Aprica; Hairudin, Hairudin (Journal of Society Bridge, 2023)
Given that the level of competition continues to be higher, many companies produce the same products, so business actors must formulate the perfect marketing policy for their survival. To determine the right marketing, it is necessary to review several factors, including product quality, price, promotion and distribution channels. This research aims to determine the effect of product quality and distribution channels on sales volume at CV. Citra Abadi (CA) Bandar Lampung. Independent variables include variable product quality, and distribution channel while the dependent variable is the sales volume. The type of data in this research use quantitative research using primary and secondary data. The population size is 60, so determine of research sample is 60 respondent. The analysis technique used is trough validity, reliability, classical asumption, hypothesis and multiple linear regression. The result of this research show that product quality and distribution channel together (simultan) have a significanteffect of 52,5% of sales volume at CV. Citra Abadi Bandar Lampung. While the remaining 42,75% is influenced by natural factor that not investugated in this research.